MENINGKATKAN KEMAMPUAN PESERTA DIDIK DALAM MENULIS TEKS ANNOUNCEMENT MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA KELAS X-TKJ DI SMK PONPES CADANGPINGGAN TAHUN PELAJARAN 2023/2024: Seprudin*, Atikah Wati, Adhi Sulandani Pangreksa - SEPRUDIN; Atikah Wati; Adhi Sulandani Pangreksa (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
This research aims to improve students' abilities in writing announcement texts using the Contextual Teaching and Learning Approach in class X-TKJ at the SMK PONPES Cadangpinggan. The method in this research is used action research which consists of: planning, implementation, observation and reflection. Based on the results of action research, it can be concluded that the Contextual Teaching and Learning Approach can improve students' Announcement Text writing skills in class X-TKJ at SMK PONPES Cadangpinggan.